PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH DIPADU MEDIA LKS SCRAMBLE DALAM MENINGKATKAN HASIL BELAJAR BIOLOGI - Moh. Mulyadi Prasetyo; Nurhidayah Nurhidayah (Jurnal Biotek, 2021)
This classroom action research aims to improve biology learning outcomes for students of the Department of Biology Education, Muslim Maros University. The study's action hypothesis was that combining a make-a-match learning model with scrambled worksheets media would increase biology learning outcomes. The objects involved in this study were 18 students. Data collection techniques in this study used the following instruments: (1) learning outcomes test sheets in each cycle and (2) activity observation sheets. The data analyzed by quantitative descriptive analysis for learning outcomes test data and qualitative analysis for student activity observation data. The results of the quantitative descriptive analysis showed that the Biology learning outcomes of students of the Biology Education Department, Muslim Maros University had an average score in the first cycle of 74.66, and the in the second cycle increased by 85.38. Qualitatively there was an improvement in student activity in the Biology learning process seen from several aspects that met in the high category. It seems like there is an increase through the application of the make a match type learning model combined with the Scramble LKS media.